IMPLEMENTASI PERDA NO. 7 TAHUN 2005 TENTANG PENGAWASAN DAN PENGENDALIAN MUATAN LEBIH (Studi Kasus Resiko Kerusakan Jalan Nasional dan Provinsi di Kota Pekanbaru) - As Juan Antoni; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Over loads is still an issue that needs special attention from the governmentand people of Riau. There needs to be an understanding of the procedures forloading of large transport vehicles loaded obey traffic in order to create a safe andcomfortable. The presence of more charge would be accompanied by the risk ofdamage to the road. Pekanbaru city with its strategic location and as the capital ofRiau province could not be separated from the problems of overloading. In fact, ifthe implementation is done with good roads such as national roads and provincialroads will be maintained in Pekanbaru condition. In fact there is still damage to theroad. Researchers refer to the implementation of the theoretical concepts in VanMeter Van Horn (Subarsono 2005). This research uses descriptive qualitativemethod of data collection techniques of observation, interviewing and researchinformants determined by snowball sampling technique. Samples taken are RiauProvincial Transport Department. By looking at the condition of national roads andprovincial roads in Pekanbaru.Keywords : Implementation , Regulation , Loads More , Damage Roa